Plan estratégico de marketing para el lanzamiento y promoción del producto "Talco medicado a base de almidón de yuca" dirigido a madres de infantes de Guayaquil. - Vera Zurita, María José (2015)
The following research intends to create an Emotional Marketing Plan that introduce a new powder made of natural components, which will be offered to Cassava Starch processing companies. This marketing plan would allow the product to compete and to position itself in the market as one of the most convenient to prevent and reduce the levels of atopic dermatitis within the infants in Guayaquil. The product Natubaby is a powder made of cassava starch, that has been created to prevent and treat the problems of atopic dermatitis in the skin of infants, becoming an innovative product, with a competitive price, and with natural components, that will give customers confidence to buy it. Guayaquil City is the area where the product will be market, the market segment is focused on mother of infants in the range of 0-2 years old. The research has taken two approaches: quantitative and qualitative, the survey and focus group were the techniques applied for data collection. The emotional marketing plan, will be utilized in order to influence the attitudes of the consumer, enhancing the attributes of the product. The Neuromarketing will be a tool that will help to reached customers, though the emotions, because the brain receives stimuli so the consumers have the desire to obtain the product. The results obtained leads to the conclusion that the direct competitor is the brand Johnson & Johnson, which is recognized in the market of products for babies, as the main choice, but not the only one.